THE EFFECTIVENESS OF PEPPERMINT AROMATHERAPY INHALATIONIN NURSING CARE FOR INEFFECTIVE AIRWAY CLEARANCE IN PULMONARY TUBERCULOSIS PATIENTS AT DRAJAT PRAWIRANEGARA HOSPITAL, BANTEN, INDONESIA: CASE STUDY - Eli Amaliyah; Syafrina, Muhamad Alfin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Background: Tuberculosis is the disease with the 13th highest mortality rate in the world and the second largest after Covid-19. Pulmonary Tuberculosis is the highest cause of death due to tuberculosis bacterial infection. Objective: This study aims to determine the effectiveness of Peppermint Aromatherapy Inhalation on nursing care for ineffective airway clearance in Pulmonary Tuberculosis patients at Drajat Prawiranegara Hospital. Methods: The research method used is qualitative research with a research design that is a case study through a Nursing Care Approach which includes nursing assessment, nursing diagnosis, nursing intervention, nursing implementation, and nursing evaluation. The subjects of this study were two patients with pulmonary tuberculosis who experienced the problem of ineffective airway clearance at RSUD Dokter Drajat Prawiranegara, Serang City, Banten, Indonesia. Results: The application of peppermint aromatherapy inhalation which was carried out three times a day for three consecutive days was found that the patient could expel phlegm and decreased respiratory frequency. Conclusion: The results of this study found that the application of peppermint aromatherapy inhalation can reduce the problem of airway clearance ineffectiveness which includes coughing up phlegm and shortness of breath in patients with pulmonary tuberculosis.